2016
DOI: 10.4103/1305-7456.195166
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health status and implication of periodic acid–Schiff diastase - a key in exfoliative cytology among diabetics mellitus patients: A case–control study

Abstract: Objectives:The objectives of the study are: (i) To determine if periodic acid–Schiff (PAS)-Diastase is an effective tool to diagnose DM noninvasively, (ii) to use three different types of staining procedures to identify the staining pattern over the exfoliated cells of normal and diabetic patients, (iii) to study the periodontal health status of DM and normal subjects.Materials and Methods:Basic questions regarding the demographic data were asked, following which community periodontal index (CPI) was recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…In our study oral epithelium in Type 2 diabetic patients on PAP smears found that there is an increase in the nuclear area and binucleation among the diabetic group which could be probably because of deficiency of Vitamin B12 or folic acid. These results were consistent with the previous studies of Alberti et al, Jajarm et al, Shareef et al and Nandita et al [7].…”
Section: Discussionsupporting
confidence: 94%
“…In our study oral epithelium in Type 2 diabetic patients on PAP smears found that there is an increase in the nuclear area and binucleation among the diabetic group which could be probably because of deficiency of Vitamin B12 or folic acid. These results were consistent with the previous studies of Alberti et al, Jajarm et al, Shareef et al and Nandita et al [7].…”
Section: Discussionsupporting
confidence: 94%